1997
DOI: 10.1007/s002469900215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Idiopathic Long QT Syndrome in Children with Congenital Deafness

Abstract: Long QT syndrome (LQTS) is characterized by prolongation of the QT interval associated with a high risk for syncope and sudden death. Jervell and Lange-Nielsen initially described LQTS in association with congenital sensorineural deafness. We have investigated the prevalence of this syndrome in a school for deaf children, evaluating by ECG 350 congenitally deaf children with an age range of 6-19 years. The corrected QT interval (QTc) was calculated by Bazett's formula. Eight children with a QTc interval >440 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Hanioglu-Kargi et al [29] found in an ophthalmologic screen of deaf pupils one Waardenburg, 1 Usher syndrome in 104 Turkish deaf pupils. Ocal et al [30] found 2 Jervell Lange Nielsen syndrome in cardiologically screened 350 Turkish deaf pupils. In our study, syndromic etiology was found in 18.0% of the entire study group and 28.61% of those with genetic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Hanioglu-Kargi et al [29] found in an ophthalmologic screen of deaf pupils one Waardenburg, 1 Usher syndrome in 104 Turkish deaf pupils. Ocal et al [30] found 2 Jervell Lange Nielsen syndrome in cardiologically screened 350 Turkish deaf pupils. In our study, syndromic etiology was found in 18.0% of the entire study group and 28.61% of those with genetic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two girls aged 14 and 15 were diagnosed with LQTS. [19] In our study, due to lack of repeated access to the patients, their ECG records available were only studied. However, in some studies, genetic analysis was conducted regarding LQTS and the patients' genotypes were studied regarding LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there has been a study published on 132 children with a hearing loss, among who 5 (3.8%) patients were diagnosed with JL-N syndrome [8]. On the other hand, in 350 Turkish children with congenital hearing loss, who were between the ages of 6 and 19 years, LQTS (according to Schwartz criteria) was present in only 2 (0.57%) patients (girls aged 14 and 15 years) [9]. In that Turkish study, the population of children was older than in our study.…”
Section: Discussionmentioning
confidence: 99%